Effectiveness of technology transfer in the search for sustainable development: The case of Qatar - Al-Saadi, R. (Cranfield University, 2010)
The Emir of Qatar firmly believes that security without development is not sustainable in the long run. Endorsed by Qatar’s top leadership, this conviction has spread contagiously to all corners of the public and private spheres, leading, in turn, numerous initiatives and massive investments directed at the development of the country. Sustainable development investments in Qatar are promising, but the process very slow amidst dynamic globalization. Technology capability is a key factor accelerating the growth of economic, social and environmental development. Hence, the aim of this dissertation is to assess the effectiveness of technology transfer in Qatar's search for sustainable development. The scope of the dissertation is confined to an analysis of certain government agencies involved in technology transfer; the government, the industry and R&D centres. The study developed a framework of measures to assess Qatari technology transfer and sustainable development, categorized into nine themes, including sustainable development, governance and internal environment, external technology resources, internal technology resource measures, absorptive capacity, value chain, value network, research and development and competitiveness. Through exploratory, descriptive and predictive research using qualitative and quantitative field surveys, along with secondary research, the study developed a framework of measures, and used it to assess the effectiveness of sustainability and technology transfer in Qatar. The study concluded that the technology transfer environment and practices in Qatar are ineffective in advancing the search for sustainable development. The study recommends the need to establish policies and priorities to facilitate sustainable development, focusing especially on technology, science and innovation. Future research should focus on in-depth case studies of specific industrial clusters as well as deepening the understanding of thematic measures of sustainability.